Facile surfactant-assisted synthesis of CTAB-incorporated MoS2 ultrathin nanosheets for efficient hydrogen evolution. Issue 20 (9th February 2016) - Guo, Zhiyan; Ma, Qingxuan; Xuan, Zongwei; Du, Fanglin; Zhong, Yang
Abstract : CTAB-incorporated MoS2 ultrathin nanosheets exhibit an excellent activity for HER with a small onset potential, a low Tafel slope, and relatively good stability. Abstract : Molybdenum disulfide (MoS2 ) has emerged as a promising electrocatalyst for catalyzing protons to hydrogen via the so-called hydrogen evolution reaction (HER). In order to enhance the HER activity, CTAB (cetyltrimethyl ammonium bromide)-incorporated MoS2 ultrathin nanosheets with high specific surface area and more catalytic active sites have been successfully synthesized via a facile surfactant-assisted hydrothermal approach. Adding CTAB to the hydrothermal process can effectively regulate both structural and electronic benefits by controllable disorder engineering and simultaneous CTAB incorporation in MoS2 catalysts, leading to a higher specific surface area, more catalytic active sites and better electrical conductivity for improving HER activity. The optimized CTAB-incorporated MoS2 ultrathin nanosheets exhibit excellent activity for HER with a small onset potential of 88 mV, a low Tafel slope of 55 mV dec −1, and relatively good stability.